(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2023)
The objective of this research is to establish the virtue of marketing strategies for a company or enterprise in order to position its brand in front of the competition and to be able to maintain its position over time. To achieve this objective a documentary research was applied, reading in various articles, bibliographies and documentaries in order to illustrate the article with the concepts, matrices and strategies suitable for its application. We came to the conclusion that if a company does not carry out a good study of its internal and external weaknesses and strengths, it will not be able to grow and remain in the market today, thus causing the bankruptcy or collapse of the enterprise.